2022
DOI: 10.1002/kpm.1707
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management and knowledge security—Building an integrated framework in the light of COVID‐19

Abstract: This paper presents a framework of knowledge risk management in the face of the COVID‐19 crisis, derived from the literature on knowledge management, knowledge security, and COVID‐19. So far, both researchers and practitioners have focused on knowledge as an asset and their efforts have been aimed at the implementation of knowledge management in various organizational contexts. However, with increasing threats related to cyberattacks or hazards associated with knowledge loss (as magnified by the COVID‐19 crisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Finally, the results on the influence of IT security on the attitude of LG’s workers toward COVID-19 were exciting, as they showed that IT security policies, in terms of importance and implementation of security guidelines ( Zieba & Bongiovanni, 2022 ), help in the public delivery of services to citizens ( Mbunge et al, 2021 ). Differences in employee perception may be due to the long and sometimes tortuous path for IT security to become an established element in organizations, as the following points out ( Georgiadou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the results on the influence of IT security on the attitude of LG’s workers toward COVID-19 were exciting, as they showed that IT security policies, in terms of importance and implementation of security guidelines ( Zieba & Bongiovanni, 2022 ), help in the public delivery of services to citizens ( Mbunge et al, 2021 ). Differences in employee perception may be due to the long and sometimes tortuous path for IT security to become an established element in organizations, as the following points out ( Georgiadou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2022; Yin et al., 2022; Zhang et al. , 2022; Zieba and Bongiovanni, 2022). The recent business context initially involved massive layoffs offsetting the negative effects of pandemic-induced recession; then, the pendulum swung to the other extreme necessitating substantial recruitment to meet increased demand driven by a post-pandemic boom.…”
Section: Introductionmentioning
confidence: 99%
“…, 2022; Lazzari et al. , 2022; Tseole and Ngulube, 2022; Zieba and Bongiovanni, 2022). The organizational challenge involves capitalizing on the very latest KM, specifically K-loss research, moving forward in this dynamic new world.…”
Section: Introductionmentioning
confidence: 99%
“…Hereinafter faculty refers to “ knowledge workers ” who create, acquire, share, and disseminate knowledge among students. Higher educational institutions had to find ways to survive by formulating and implementing resilient strategies for higher educational institutions (Rana et al, 2020 ; Zieba & Bongiovanni, 2022 ). One of the biggest challenges educational institutions face during the crisis is to switch from in‐class to web‐based online education.…”
Section: Introductionmentioning
confidence: 99%